2017
DOI: 10.4102/sajim.v19i1.776
|View full text |Cite
|
Sign up to set email alerts
|

Factors negatively influencing knowledge sharing in software development

Abstract: Background: ‘Knowledge is power’ and software developing organisations are dependent on knowledge to achieve and maintain a competitive advantage. Subsequently, knowledge sharing is a key factor for modern software developing organisations to succeed in today’s competitive environment. For software developing organisations to reach their goals and objectives, knowledge sharing – and in particular the sharing of useful knowledge – needs to be targeted. To promote knowledge sharing, factors influencing knowledge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
(48 reference statements)
0
4
0
Order By: Relevance
“…Regarding knowledge sharing as a way of knowledge creation and management, self-confidence emerged as the most important personal trait that leads the knowledge bearer to share their knowledge widely and openly, in addition to being linked to increased sales (Li et al, 2006). Lack of self-confidence apparently creates a barrier to knowledge sharing because it perhaps potentially leads to narrow-mindedness and fearfulness of losing status or job or position as a consequence of giving away knowledge, an important source of power (Khoza & Pretorius, 2017;Schwartz & Bilsky, 1987;Wang & Noe, 2010). Self-confidence was regarded as the outcome of education and interpersonal relationships.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding knowledge sharing as a way of knowledge creation and management, self-confidence emerged as the most important personal trait that leads the knowledge bearer to share their knowledge widely and openly, in addition to being linked to increased sales (Li et al, 2006). Lack of self-confidence apparently creates a barrier to knowledge sharing because it perhaps potentially leads to narrow-mindedness and fearfulness of losing status or job or position as a consequence of giving away knowledge, an important source of power (Khoza & Pretorius, 2017;Schwartz & Bilsky, 1987;Wang & Noe, 2010). Self-confidence was regarded as the outcome of education and interpersonal relationships.…”
Section: Discussionmentioning
confidence: 99%
“…According to Schierjott et al (2018), employees tend to rely on their relationships with peers to accumulate knowledge. Others argue that trust in interpersonal relationships (Chen et al, 2014;Khoza & Pretorius, 2017;Lu et al, 2006) facilitates knowledge sharing (Taura & Radicic, 2019) and motivators to share knowledge (Holste & Fields, 2010). Nonaka et al (2000, p. 28) note the importance of "strong love, caring and trust amongst organisational members."…”
Section: Interpersonal Relationshipsmentioning
confidence: 99%
“…Researchers have confirmed the importance of knowledge sharing in organizations (Giampaoli, Ciambotti, & Bontis, 2017). Knowledge results in power for organizations and the individuals within (Khoza & Pretorius, 2017) 2017). The establishment of a centralized resource center is a great method for transferring knowledge to employees; however, project team members will also need adequate training and development to deliver effective knowledge management (McNealy, 2017).…”
Section: Discussionmentioning
confidence: 96%
“…"Organizational leaders must build a culture where project management business leaders are free to use their knowledge management strategies to transfer knowledge to their project team members for successful project outcomes; thus, increasing the competitive advantage of the overall organization" (McNealy, 2017, p.106). The purpose of knowledge management is to generate results (Serrat, 2017); therefore, knowledge management strategies are vital for the transfer of knowledge (Khoza & Pretorius, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In a survey, it was found that documentation and transfer of project knowledge is the most burdensome tasks for project managers, and they express a strong desire to remove it from their to-do lists (Harrin, 2022). Several issues and concerns have been identified to influence ITPMs' unwillingness to share their experiences, expertise, and lessons learned from previous projects, such as reward and promotions (Chelagat et al, 2019;Jhamba & Steyn, 2021;Nakayama et al, 2021), communication barriers (Alwahdani, 2019;Ren et al, 2018), time urgency (Avença et al, 2023;Khoza & Pretorius, 2017;Zhao et al, 2015), job security (Khoza & Pretorius, 2017;Pietruszka-Ortyl et al, 2021), resistance to change (Beste, 2023;Khoza & Pretorius, 2017), technological limitation (Mirzaee & Ghaffari, 2018;Nidhra et al, 2013;Pietruszka-Ortyl et al, 2021), and the need for technical expertise (Alwahdani, 2019;Chelagat et al, 2019;Liu et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%